PROBLEMS OF ADAPTATION OF THE UKRAINE’S LEGISLATION TO THE EU LEGISLATION: THE HUMAN SYNTHETIC APPROACH - Solodovnikova, Khrystyna K. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Aim: is to determine, with the help of socio-psychological approach, the place and role of the person as the acquirer and implementer of fundamental rights and freedoms in the context of the processes of European integration of Ukraine. Methods of research: general scientific research methods: analysis, synthesis, refinement, and special methods: juristical – comparative legal, judicial statistics, interpretation of the norms of law; psychological – content analysis of documents. Discussion: analyzes the scientific approaches of possibilities to use the socio-psychological approach in the law. In particular, in connection with the signing of the agreement between Ukraine and the European Union, at the time of rethinking the place and the role of a person in law. This problem was clearly manifested, in particular, in the context of solving scientific and practical issues concerning the situation with the negative consequences of terrorist acts in the Donbas. Conclusions and perspectives of research: we found out that if we will using the socio-psychological approach in Ukraine it will lead to the revaluation about the place and the role of a person in the law.